Willingness to Pay for Safe Chicken Meat in Bangladesh: A Contingent Valuation Approach - Sourav Mohan Saha; Md. Masudul Haque Prodhan; Md. Shahidur Rahman; A.B.M. Mahfuzul Haque; Khandkar Iffah; Md. Akhtaruzzaman Khan (Journal of Food Quality)
The poultry meat industry is primarily dominated by broilers, and conventional broiler meat is claimed to be malicious to human health and environment since it is produced using hazardous feeds and other dietary supplements. This study aimed to evaluate consumers’ willingness to pay (WTP) for safe broiler chicken meat following a contingent valuation model (CVM). Also, consumers’ consumption and different types of perceptions on safe broiler meat were assessed from the data collected among 300 consumers in Bangladesh. Consumers’ health and environmental perception of safe broiler meat are found to be high, indicating that they are more concerned about these attributes in the case of consuming broiler meat. The results reveal that conventional broiler meat losses its appeal to consumers after a certain income level and is mainly consumed by lower- and middle-income groups. This study divulges a unanimous demand for safe broiler meat among the consumers who intend to consume about 36% higher than their present consumption level if the availability was ensured in their local market. The average WTP premium for safe broiler meat is estimated to be about BDT 39.87 per kg. The consumers’ WTP is positively influenced by their education, income level, the current consumption of broiler chicken meat, health perception, and taste and nutrition perception. This study recommends meat producers, entrepreneurs, and farmers adjust their production and marketing plans by incorporating suitable quality control procedures to meet the unfilled consumer demand for safer broiler meat. Besides, slow-growing safer broiler chicken needs to be introduced to improve meat’s taste and nutritional aspects.